UMA NOVA ESPÃ‰CIE DE ð˜Œð˜³ð˜ªð˜°ð˜ð˜¶ð˜´ DO BRASIL (Orthoptera, Tettigoniidae, Copiphorinae) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA NOVA ESPÃ‰CIE DE ð˜Œð˜³ð˜ªð˜°ð˜ð˜¶ð˜´ DO BRASIL (Orthoptera, Tettigoniidae, Copiphorinae)